Preventing burnout from moral distress among prehospital emergency personnel through action research and targeted clinical ethics support - Lotte Huniche; Louise Milling; Daniel Wittrock; Søren Mikkelsen; Henriette Bruun (Scientific Reports)
Abstract Ethical challenges are integral to health care and are associated with moral distress among health professionals. Moral distress can turn into burnout with a range of negative effects for professionals, patients, relatives, collaborators, and the organisation. Based on action research a focus group study was conducted inclucing prehospital personnel from the emergency services in the Region of Southern Denmark. Results showed that ethical challenges arise in contexts of (1) caring for patients, (2) managing organisational demands, (3) collaborating. Ethical challenges are addressed informally among personnel in emergency vehicles, at ambulance stations, outside working hours, and ocationally involve family or friends with a background in healthcare. Prehospital physicians have the added opportunity to address ethically sensitive issues during monthly meetings. Voicing ethical challenges presupposes confidence, trust, and feeling safe in relation to colleagues, management, and the organisation. Existing forms of ethics support do not lend themselves to the present organisational setup of the studied emergency services. Targeted clinical ethics support initiatives are needed to address moral distress, prevent burnout, and build a supportive working environment. Initiatives must be developed collaboratively and tested bottom-up to identify and eliminate barriers for implementation.